Effects of Electroacupuncture on Benign Prostate Hyperplasia Patients with Lower Urinary Tract Symptoms: A Single-Blinded, Randomized Controlled Trial. (6th February 2011) - Yu, Jung-Sheng; Shen, Kun-Hung; Chen, Wen-Chi; Her, Jiann-Shyan; Hsieh, Ching-Liang
Abstract : We tested the effect of electroacupuncture (EA) on lower urinary tract symptoms (LUTS) in benign prostatic hyperplasia (BPH) patients. A total of 42 BPH patients with LUTS were randomly assigned to either the EA group (EG), received 2 Hz EA for 20 min twice/week for a total of twelve treatments, or a sham EA group (CG), received sham EA. The increase of voiding volume, average flow rate, and maximal flow rate in the EG were32.2 ± 104.4 mL, 1.2 ± 1.6 mL/sec, and2.3 ± 3.7 mL/sec, respectively, from baseline value (before EA) using the measurement of an uroflowmetry. These increases were greater than− 37.9 ± 120.4, − 0.22 ± 2.7, and− 0.3 ± 4.3, respectively, in the CG (P = . 038, .026, and .030, resp.). The changes of prostate special antigen and international prostatic symptom score were not significantly different between two groups (P = . 573, .175, resp.), suggesting the clinical improvement of 2 Hz EA was quite limited to the LUTS of patients with BPH.